Spatial and Temporal Patterns of Phlebotominae Sand Flies (Diptera: Psychodidae) in a Cutaneous Leishmaniaisis Focus in Northern Argentina - Salomón, Oscar Daniel (2004)
Phlebotomine sand ßies (Diptera: Psychodidae) were captured in an area of Argentina endemic for American cutaneous leishmaniasis (ACL). A total of 44,944 ßies were collected during a 130-wk interepidemic period from 1990 through 1993. These sand ßies included Lutzomyia neivai (Pinto) (97.8%), Lutzomyia migonei (Franc¸a) (1.2%), Lutzomyia cortelezzii (Bre`thes) (0.8%), Lutzomyia shannoni (Dyar) (0.1%), and Lutzomyia punctigeniculata (Floch and Abonnenc) (0.1%). Lutzomyia neivai was more abundant in secondary forests and peridomestic environments associated with human cases than in primary forest or xeric thorn scrub areas. Time series analyses of species densities suggested a bimodal or trimodal annual pattern related to rainfall peaks, a 5-wk reproductive cycle, and peridomestic local populations that were located adjacent to secondary forests. In general, sand ßy abundance was correlated with the rainfall of the previous year. Lutzomyia neivai spatial distributions were consistent with ACL incidence patterns during the study and in the recent outbreaks in Argentina. However, Lu. migonei also may be involved in peridomestic transmission. Our results suggest that there is a need for improved, long-term surveillance of sand ßies and ACL cases, as well as development of effective intervention strategies.